Sputter Deposition of Cuprous and Cupric Oxide Thin Films Monitored by Optical Emission Spectroscopy for Gas Sensing Applications - Nayan, N; Sandan, MZ; Wei, LJ; Ahmad, MK; Lias, J; Shakaff, AYM; Zakaria, A; Zain, AFM (Elsevier Science Bv, 2024)
Indexed by WOS